Hubungan antara Percaya Diri dengan Motivasi Berprestasi pada Ekstrakurikuler Paskibra di Surabaya (SUKMA : Jurnal Penelitian Psikologi, 2020)
The study aims to determine the correlation between self confidence and achievement motivation of Paskibra extracurricular in Surabaya. The type of research is a quantitative type of correlational research. The subjects were 99 junior and senior high school students who joined the Paskibra extracurricular team in Surabaya. Measuring instruments in this study used 2 scales, the achievement motivation scale and the self confidence scale. Data analysis uses the Product Moment analysis method. Product Moment analysis results showed that the variable of self confidence with achievement motivation correlates very significantly. It shows that hypothesis proposed by the researcher is accepted. Keywords: Achievement motivation, Self Confidence, Paskibra.